"A lot of people are paying like 5 a week for 20 years": New Zealand lawyers, discounts, and payment plans. Issue 3 (2nd September 2021) - Toy-Cronin, Bridgette; Choe, Louisa; Stewart, Kayla
ABSTRACT: The unaffordability of legal assistance is a widespread problem in New Zealand, as it is in many other common law countries. One way legal assistance is made more accessible is by lawyers offering discounting and payment plans. There is very limited research about how these practices operate and whether they are effective at delivering services to people in need. This article reports the results of a mixed-methods study to investigate New Zealand lawyers' attitudes to these services, the extent to which they offered them, and how they were structured. The data showed that most lawyers offered discounts and payment plans. The decision to offer these services was generally made on a case-by-case basis and to clients who individual lawyers, in their discretion, considered worthy cases. The amount of the discount was often benchmarked to the legal aid rate but this could still put legal fees out of reach for many clients. While payment plans could offer liquidity for clients to access justice, they could also be problematic, drawing clients into long term debt. Starting with the client's budget and determining legal fees from that starting point delivers more affordable legal services than the emphasis on discounting and payment plans.